A PRIMINALRY DETERMINATION OF FACTORS EFFECTING FEMALE TRAVEL DEMAND, PATTERN, AND BEHAVIOR IN THE KINGDOM OF SAUDI ARABIA - Alshabibi, Nawaf (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to priminalry identify and determine factors effects female travel pattern, demand, and behavior in the Kingdom of Saudi Arabia. The study came to assess the royal act by the king to allow females to drive private cars in the Kingdom. The study proves in literatures worldwide that many studies came to demonstrate and distinguish between male and female driving pattern, demand, and behavior. Data of the study has collected through a Delphi technique by a panel of expert working in several private and governmental sectors in the eastern province of the kingdom of Saudi Arabia. A questionnaire of 77 questions has developed for data collection and interviewing 125 experts. Coding style has been used in Excel spreadsheet for data extraction and analysis. The data has been summarized in tables to present the percentages of responses. The study summarizes a group of priminalry factors effect in female driving pattern, demand, and behavior in the Kingdom of Saudi Arabia in different aspects such as economic, social, environmental, planning, organizational, transportation, and traffic regulation.